Contemporary art, systems, and the aesthetics of dispersion - Halsall, Francis (Abingdon, Oxon : Routledge, 2023)
Using five case studies of contemporary art, this book uses ideas of systems and dispersion to understand identity and experience in late capitalism. This book considers five artists who exemplify contemporary art practice: Seth Price; Liam Gillick; Martin Creed; Hito Steyerl; and Theaster Gates. Given the diversity of materials used in art today, once-traditional artistic mediums and practices have become obsolete in describing what artists do today. Francis Halsall argues that, in the face of this obsolescence, the ideas of system and dispersion become very useful in understanding contemporary art. That is, practitioners now can be seen to be using whatever systems of distribution and display are available to them as their creative mediums. The two central arguments are first that any understanding of what art is will always be underwritten by a related view of what a human being is; and second that these both have a particular character in late capitalism or, as is named here, the Age of Dispersion. The book will be of interest to scholars and students working in art history, contemporary art, studio art, and theories of systems and networks.
Keywords: Art and society -- History -- 21st century; Art, Modern -- 21st century; ART / History / Contemporary (1945-); ART / American / General